Modelos de gestión pedagógica, en zonas de atención prioritaria: análisis de una experiencia - Cerdas Montano, Virginia; Marín Calderón, Adyeri; Vargas Jiménez, Ileana (Revista Electrónica Educare, 2008)
The “División de Educación para el Trabajo del CIDE, Universidad Nacional”, started a research project for the benefit of educational administrators. The aim of the project is to devise a methodology for the implementation of pedagogical management models, useful to confront the necessities of each educational center. The results are the product of a series of action-reflection-action analysis. The project is being now developed in nine schools located in zones of prioritized focus. Among the most outstanding achievements was the development of their own pedagogical management models, pertinent to the school according to each context. It is expected that the findings will work as a contribution for management in educational institutions.